Correlation between productivity and grain quality of spring durum wheat and meteorological factors in the southern forest-steppe of the Western Siberia - М. G. Evdokimov; V. S. Yusov; I. V. Pakhotina (Зерновое хозяйство России, 2020)
The purpose of the current study was to identify the effect of meteorological factors on productivity and grain quality indicators of spring durum wheat in the conditions of Western Siberia. The research was carried out in the FSBSI “Omsk Agricultural Research Center” in 1981-2019. The object of the study was the durum spring wheat variety ‘Almaz', which was tested in the nurseries of the Competitive Variety Testing according to such traits as productivity, nature weight, hardness of grain, protein and gluten percentage, IDK, pasta color. The average productivity through the years of study was 2.51 t/ha, the differences between indicators in the unfavorable (1.54 t/ha) and favorable (3.48 t/ha) years were 1.94 t/ha. The grain nature weight in the years with good humidity was on 22g/l larger than in the arid years, the hardness of grain was on 5% larger. The protein and gluten percentage, the pasta color value was larger in the unfavorable climatic years (on 1.60%, 4.3%, 0.2 points, respectively), compared with favorable ones. There has been found that the productivity was positively associated with the precipitation in May and the 1st decade of July, relative humidity in May and June; there was established a negative correlation with air temperature in June. The nature weight of grain had a negative dependence on precipitation (1st and 2nd decades) and relative humidity in August for all decades. The hardness of grain was positively affected by temperature in May and precipitation in July (1st decade). The protein percentage in grain was negatively affected with precipitation and relative air humidity in May, June and July (1st and 3rd decades). Average daily temperatures in May and July had a positive effect on the protein percentage in grain. The gluten percentage had a positive correlation with the temperature in May and in the third decade of July. A negative dependence of this indicator was established with precipitation in May, June and the 3rd decade of July, with the relative humidity in May, June, July (1st and 3rd decades), August (3rd decade). The pasta color was negatively dependent on precipitation and relative humidity in July (3rd decade) and August (1-2nd decades).